2020
DOI: 10.1503/cjs.009219
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality conferences in general surgery: a narrative systematic review

Abstract: Background: In medical and surgical departments around the world, morbidity and mortality conferences (MMC) serve dual roles: they are cornerstones of quality-improvement programs and provide timely opportunities for education within the urgent context of clinical care. Despite the widespread adoption of MMCs, adverse events and preventable errors remain high or incompletely characterized, and opportunities to learn from and adjust to these events are frequently lost. This review examines the published literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
(134 reference statements)
0
16
0
Order By: Relevance
“…Morbidity and mortality meetings, malpractice claims, medical record review, practice surveillance, audits and incident reporting systems are examples of methods used to capture information relating to patient safety incidents. [9][10][11][12] All have varying ability to identify different types and causes of incidents. 13 Incident reporting systems provide a structure for incident processing and analysis, generating unique insights from the perspective of the practice team.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morbidity and mortality meetings, malpractice claims, medical record review, practice surveillance, audits and incident reporting systems are examples of methods used to capture information relating to patient safety incidents. [9][10][11][12] All have varying ability to identify different types and causes of incidents. 13 Incident reporting systems provide a structure for incident processing and analysis, generating unique insights from the perspective of the practice team.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity and mortality meetings, malpractice claims, medical record review, practice surveillance, audits and incident reporting systems are examples of methods used to capture information relating to patient safety incidents 9–12 . All have varying ability to identify different types and causes of incidents 13 .…”
Section: Introductionmentioning
confidence: 99%
“…quality improvement and education). Cases should be selected based on predefined criteria and discussed using a standardized presentation format that is succinct, limiting both clinical history and literature review to only pertinent details to ensure ample time for discussion and analysis of the root causes of the adverse events [ 26 ]. Bal et al [ 4 , 5 , 7 ] confirmed that a well-structured and well-documented presentation allows to bring up all possible underlying contributing factors as a preliminary step to a systematic approach allowing a deep-dive into the root causes of adverse events identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, MMRs should not be just an opportunity to deliver theoretical knowledge, strategies need to be developed to translate error analysis into meaningful QI initiatives [ 26 ]. This includes setting clear goals and measuring implementation which provides quantitative assessment of the quality improvement achieved by MMRs.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity and mortality reviews when conducted at a regular frequency, through a standardized procedure and case presentation with clearly defined goals [15] , [16] , [17] can identify system-based issues and allow for ample analysis of the root causes and possible underlying contributing factors of the adverse events [18] and thus, shifting MMR towards a quality improvement scope.…”
Section: Discussionmentioning
confidence: 99%